A thermosetting resin ceramic composite material and its preparation method and application
Through the thermosetting resin ceramic composite material with a specific core-shell structure, combined with the technology of coupling modified nanoceramic powder and thermosetting resin, the problem of tight bonding of nanoceramic powder and material refractive index is solved, and the efficient curing performance of ceramic photocuring printing is achieved.
Patent Information
- Application Number
- CN202411770006.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The prior art is difficult to effectively bond nanoceramic powder particles and make the surface refractive index of the material system meet the requirements of ceramic photocuring printing, resulting in poor curing performance.
The thermosetting resin ceramic composite material with a specific core-shell structure is used to form dense composite microspheres by coupling the modified nanoceramic powder with the first thermosetting resin, and the optical characteristics and curing properties of the material are improved by coating the second thermosetting resin.
It realizes the close bonding of nanoceramic powder, improves the density and photocuring performance of composite materials, and is suitable for ceramic photocuring printing.
Smart Images

Figure CN119241218B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic photocuring additive manufacturing, and in particular relates to a thermosetting resin ceramic composite material and a preparation method and application thereof. Background Art
[0002] Ceramic photocuring printing technology is one of the most important and mature ceramic additive manufacturing technologies, and has a broad application market space in the fields of aerospace industry, automobile industry, machinery industry, power electronics industry, biomedical industry, building materials and decorative materials. Nano ceramic powder materials have high surface activity and excellent sintering activity. They should be the first choice for raw materials in ceramic photocuring printing. However, it is currently difficult to prepare high solid phase and low viscosity photocuring ceramic slurry with nano ceramic powder, and it is difficult to directly apply it to ceramic photocuring printing. The existing improvement technology agglomerates nano ceramic powders to form coarser agglomerates to reduce their surface activity, so that relatively high solid phase and low viscosity photocuring ceramic slurry can be prepared. However, the density of the agglomerates is low, there are gaps between nano ceramic powder particles, the bonding force is poor, and the agglomerates are easily broken in the configuration of photocuring ceramic slurry. In addition, the high refractive index characteristics of many nano ceramic material systems currently lead to poor curing performance, and even if they are prepared into photocuring ceramic slurry, they are difficult to print and form. Therefore, there is an urgent need for a technology that can effectively combine nano-ceramic powder particles tightly and make the surface refractive index of the material system meet the requirements of ceramic photocuring printing. Summary of the invention
[0003] The present invention aims to improve at least one technical problem in the background technology.
[0004] In a first aspect, the present invention provides a thermosetting resin ceramic composite material, which includes a core and a shell layer, wherein the core includes a composite microsphere formed of a first material, the first material includes a coupled modified nano-ceramic powder and a first thermosetting resin, the coupled modified nano-ceramic powder is obtained by coupling modification of the nano-ceramic powder, and the coupling modification includes the following steps: mixing the nano-ceramic powder with water, adding a coupling agent, ball milling, and drying to obtain the coupled modified nano-ceramic powder; the shell layer includes a second thermosetting resin.
[0005] The present invention proposes a thermosetting resin ceramic composite material with a specific core-shell structure. Regarding the inner core of the thermosetting resin ceramic composite material of the present invention, nano-ceramic powder particles are bonded and agglomerated into larger composite microspheres through the solidification of a first thermosetting resin, and the nano-ceramic powder particles are more tightly bonded, thereby improving the density of the composite microspheres. In addition, the nano-ceramic powder is coupled and modified, thereby improving the compatibility of the nano-ceramic particles with the first thermosetting resin. Therefore, the present invention can achieve the granulation effect of nano-powders, and the diameter of the composite microspheres obtained by granulation reaches 1-10 microns. Regarding the shell layer of the thermosetting resin ceramic composite material of the present invention, the second thermosetting resin coats the composite microspheres formed by combining the nano-ceramic particles and the first thermosetting resin. The presence of the first thermosetting resin component in the composite microspheres makes the composite microspheres also have good compatibility with the second thermosetting resin of the shell layer. The presence of the shell layer further improves the density of the thermosetting resin ceramic composite material prepared by the present invention; in addition, the optical properties of the surface of the coupled modified nano-ceramic powder are changed by coating with the second thermosetting resin of the shell layer, and its surface refractive index is reduced, which can effectively improve its photocuring performance.
[0006] Furthermore, the raw materials of the first material include: coupling modified nano-ceramic powder, a first thermosetting resin monomer and a first curing agent; the second thermosetting resin is formed by the second material, and the raw materials of the second material include: a second thermosetting resin monomer and a second curing agent; the coupling modified nano-ceramic powder is obtained by modifying the nano-ceramic powder with a coupling agent.
[0007] Furthermore, by weight, the nano-ceramic powder is 100 parts, the coupling agent is 0.5-2 parts, the first thermosetting resin monomer is 5-30 parts, the first curing agent is 0.05-0.3 parts, the second thermosetting resin monomer is 2-5 parts, and the second curing agent is 0.02-0.05 parts.
[0008] Furthermore, the nano-ceramic powder is at least one of nano-alumina ceramic powder, nano-zirconia ceramic powder, nano-nickel oxide ceramic powder, nano-silicon carbide ceramic powder, nano-aluminum nitride ceramic powder and nano-silicon nitride ceramic powder; the coupling agent is at least one of methyl silane, epoxy silane, γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane and isopropoxy dioleyloxy (dioctylphosphoyloxy) titanate; the first thermosetting resin monomer and the second thermosetting resin monomer are independently selected from at least one of tripropylene glycol diacrylate and epoxy resin; the first curing agent and the second curing agent are both dibenzoyl peroxide.
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned thermosetting resin ceramic composite material, comprising the following steps:
[0010] Conducting coupling modification on the nano-ceramic powder to obtain coupled modified nano-ceramic powder;
[0011] Dispersing the coupled modified nano-ceramic powder in the first anhydrous ethanol, adding the first thermosetting resin monomer and the first curing agent, and mixing well to obtain slurry A;
[0012] Dissolving the stabilizer in water to obtain slurry B;
[0013] Add slurry A dropwise into slurry B, and heat until the first anhydrous ethanol is completely evaporated to obtain slurry C;
[0014] Continue heating the slurry C to solidify the first thermosetting resin monomer to obtain slurry D;
[0015] Adding a second anhydrous ethanol, a second thermosetting resin monomer and a second curing agent to slurry D, heating until the second anhydrous ethanol is completely evaporated, and then continuing to heat to cure the second thermosetting resin monomer to obtain slurry E;
[0016] The slurry E is subjected to hot filtration and hot water washing in sequence, the hot filtration temperature is 60°C-80°C, the hot water temperature is 60°C-80°C, and after hot filtration and hot water washing, it is dried to obtain a thermosetting resin ceramic composite material.
[0017] In the preparation method of the thermosetting resin ceramic composite material of the present invention, an evaporation organic phase emulsification technology is adopted. After the first anhydrous ethanol is completely evaporated, the composite microspheres formed by the coupled modified nano-ceramic powder and the first thermosetting resin form uniformly dispersed emulsified particles in the water solvent. The emulsified particles are in a free suspension state in the water solvent space. The free suspension state and the surface tension make the composite microspheres more tightly combined, improve the density of the composite microspheres, and also improve the sphericity; in the curing process of the first thermosetting resin, the free suspension state and the surface tension make the first thermosetting resin shrink freely, so that the composite microspheres are further tightly combined and the density of the composite microspheres is further improved; after the curing of the first thermosetting resin is completed, the present invention also introduces a second thermosetting resin for secondary emulsification and curing, and coats the composite microspheres formed by the coupled modified nano-ceramic powder and the first thermosetting resin, so as to obtain a high-density thermosetting resin ceramic composite material, and reduce the surface refractive index of the coupled modified nano-ceramic powder, effectively improving its photocuring performance.
[0018] The filtration and washing in the preparation method of the thermosetting resin ceramic composite material of the present invention are hot filtration and hot water washing respectively. The use of hot filtration and hot water washing can improve the dispersibility of the thermosetting resin ceramic composite material, avoid the powder material from agglomerating into blocks due to poor dispersibility, and the powder material can be used directly without crushing to ensure good optical properties of the material surface.
[0019] Furthermore, in parts by weight, the nano-ceramic powder is 100 parts, the coupling agent is 0.5-2 parts, the first anhydrous ethanol is 80-120 parts, the first thermosetting resin monomer is 5-30 parts, the first curing agent is 0.05-0.3 parts, the second anhydrous ethanol is 5-10 parts, the second thermosetting resin monomer is 2-5 parts, and the second curing agent is 0.02-0.05 parts.
[0020] Furthermore, in slurry B, the mass ratio of stabilizer to water is (1-3): (500-1000), and the stabilizer is polyvinyl pyrrolidone or polyvinyl alcohol.
[0021] Furthermore, the curing time of the first thermosetting resin monomer is 2 hours to 4 hours, and the curing time of the second thermosetting resin monomer is 1 hour to 3 hours.
[0022] In a third aspect, the present invention provides a use of the above-mentioned thermosetting resin ceramic composite material in ceramic photocuring printing.
[0023] Beneficial effects of the present invention: The present invention obtains a thermosetting resin ceramic composite material with a specific core-shell structure by combining evaporation organic phase emulsification technology, curing technology and secondary emulsification and curing technology, realizes the granulation of nano-ceramic powder, and the sphericity and density after granulation are more advantageous. At the same time, the surface optical properties of the nano-ceramic powder are also improved, and it can be promoted and applied in the field of ceramic photocuring additive manufacturing technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is an electronic photograph of the thermosetting resin ceramic composite material obtained in Example 1;
[0025] Figure 2 The present invention is a flow chart of the preparation method of the thermosetting resin ceramic composite material. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0027] The preparation process of thermosetting resin ceramic composite materials in the following content is as follows Figure 2 shown.
[0028] Example 1
[0029] A thermosetting resin ceramic composite material comprises raw materials by weight: 100 parts of nano zirconium oxide ceramic powder, 1 part of gamma-glycidyloxypropyltrimethoxysilane, 23 parts of tripropylene glycol diacrylate, and 0.23 parts of dibenzoyl peroxide.
[0030] The preparation method is as follows:
[0031] 100 parts by weight of nano-zirconia ceramic powder was mixed with 100 parts by weight of water, 1 part by weight of γ-glycidyloxypropyltrimethoxysilane was added, ball-milled at 400 rpm for 2 hours, and dried to obtain coupled modified nano-zirconia ceramic powder;
[0032] Dispersing the coupled modified nano-zirconia ceramic powder in 100 parts by weight of anhydrous ethanol, adding 20 parts by weight of tripropylene glycol diacrylate and 0.2 parts by weight of dibenzoyl peroxide, and mixing well to obtain slurry A;
[0033] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0034] Slurry A was dripped into slurry B, and heated at 65°C until anhydrous ethanol was completely evaporated to obtain slurry C;
[0035] The slurry C was further heated at 90° C. for 3 h to solidify the tripropylene glycol diacrylate to obtain slurry D;
[0036] 5 parts by weight of anhydrous ethanol, 3 parts by weight of tripropylene glycol diacrylate and 0.03 parts by weight of dibenzoyl peroxide were added to slurry D, and the mixture was heated at 65° C. until the second anhydrous ethanol was completely evaporated, and then heated at 90° C. for 2 h to cure the tripropylene glycol diacrylate, thereby obtaining slurry E;
[0037] The slurry E was heated to 60°C and then filtered. After filtering, the filter residue was washed 5 times with 80°C water, and then dried after washing 5 times to obtain a powdered thermosetting resin ceramic composite material. The electronic photo is shown in FIG. Figure 1 shown.
[0038] Example 2
[0039] A thermosetting resin ceramic composite material comprises raw materials by weight: 100 parts of nano zirconium oxide ceramic powder, 1 part of gamma-glycidyloxypropyltrimethoxysilane, 27 parts of tripropylene glycol diacrylate, and 0.27 parts of dibenzoyl peroxide.
[0040] The preparation method is as follows:
[0041] 100 parts by weight of nano-zirconia ceramic powder was mixed with 100 parts by weight of water, 1 part by weight of γ-glycidyloxypropyltrimethoxysilane was added, ball-milled at 400 rpm for 2 hours, and dried to obtain coupled modified nano-zirconia ceramic powder;
[0042] Dispersing the coupled modified nano-zirconia ceramic powder in 100 parts by weight of anhydrous ethanol, adding 25 parts by weight of tripropylene glycol diacrylate and 0.25 parts by weight of dibenzoyl peroxide, and mixing well to obtain slurry A;
[0043] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0044] Slurry A was dripped into slurry B, and heated at 65°C until anhydrous ethanol was completely evaporated to obtain slurry C;
[0045] The slurry C was further heated at 90° C. for 4 h to solidify the tripropylene glycol diacrylate to obtain slurry D;
[0046] 5 parts by weight of anhydrous ethanol, 2 parts by weight of tripropylene glycol diacrylate and 0.02 parts by weight of dibenzoyl peroxide were added to slurry D, and the mixture was heated at 65° C. until the second anhydrous ethanol was completely evaporated, and then heated at 90° C. for 1 h to cure the tripropylene glycol diacrylate, thereby obtaining slurry E;
[0047] The slurry E was heated to 60° C. and then filtered. After filtering, the filter residue was washed five times with hot water at 80° C. and then dried to obtain a powdered thermosetting resin ceramic composite material.
[0048] Example 3
[0049] A thermosetting resin ceramic composite material comprises raw materials by weight: 100 parts of nano zirconium oxide ceramic powder, 1 part of gamma-glycidyloxypropyltrimethoxysilane, 15 parts of tripropylene glycol diacrylate, and 0.15 parts of dibenzoyl peroxide.
[0050] The preparation method is as follows:
[0051] 100 parts by weight of nano-zirconia ceramic powder was mixed with 100 parts by weight of water, 1 part by weight of γ-glycidyloxypropyltrimethoxysilane was added, ball-milled at 400 rpm for 2 hours, and dried to obtain coupled modified nano-zirconia ceramic powder;
[0052] Dispersing the coupled modified nano-zirconia ceramic powder in 100 parts by weight of anhydrous ethanol, adding 10 parts by weight of tripropylene glycol diacrylate and 0.1 parts by weight of dibenzoyl peroxide, and mixing well to obtain slurry A;
[0053] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0054] Slurry A was dripped into slurry B, and heated at 65°C until anhydrous ethanol was completely evaporated to obtain slurry C;
[0055] The slurry C was further heated at 90° C. for 2 h to solidify the tripropylene glycol diacrylate to obtain slurry D;
[0056] 5 parts by weight of anhydrous ethanol, 5 parts by weight of tripropylene glycol diacrylate and 0.05 parts by weight of dibenzoyl peroxide were added to slurry D, and the mixture was heated at 65° C. until the second anhydrous ethanol was completely evaporated, and then heated at 90° C. for 3 h to cure the tripropylene glycol diacrylate, thereby obtaining slurry E;
[0057] The slurry E was heated to 60° C. and then filtered. After filtering, the filter residue was washed five times with hot water at 80° C. and then dried to obtain a powdered thermosetting resin ceramic composite material.
[0058] Example 4
[0059] A thermosetting resin ceramic composite material comprises the following raw materials by weight: 100 parts of nano-alumina ceramic powder, 1.5 parts of gamma-aminopropyltriethoxysilane, 32 parts of tripropylene glycol diacrylate, and 0.32 parts of dibenzoyl peroxide.
[0060] The preparation method is as follows:
[0061] 100 parts by weight of nano-alumina ceramic powder was mixed with 80 parts by weight of water, 1.5 parts by weight of γ-aminopropyltriethoxysilane was added, ball-milled at 400 rpm for 2 h, and dried to obtain coupled modified nano-alumina ceramic powder;
[0062] Dispersing the coupled modified nano-alumina ceramic powder in 110 parts by weight of anhydrous ethanol, adding 28 parts by weight of tripropylene glycol diacrylate and 0.28 parts by weight of dibenzoyl peroxide, and mixing well to obtain slurry A;
[0063] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0064] Slurry A was dripped into slurry B, and heated at 65°C until anhydrous ethanol was completely evaporated to obtain slurry C;
[0065] The slurry C was heated at 80° C. for 4 h to solidify the tripropylene glycol diacrylate to obtain slurry D.
[0066] 5 parts by weight of anhydrous ethanol, 4 parts by weight of tripropylene glycol diacrylate and 0.04 parts by weight of dibenzoyl peroxide were added to slurry D, and the mixture was heated at 65° C. until the second anhydrous ethanol was completely evaporated, and then heated at 80° C. for 2.5 h to cure the tripropylene glycol diacrylate, to obtain slurry E;
[0067] The slurry E was heated to 70° C. and then filtered. After filtering, the filter residue was washed 5 times with hot water at 70° C. and then dried to obtain a powdered thermosetting resin ceramic composite material.
[0068] Example 5
[0069] A thermosetting resin ceramic composite material comprises, by weight, 100 parts of nano silicon nitride ceramic powder, 1 part of isopropoxy dioleyl acyloxy (dioctyl phosphate acyloxy) titanate, 21 parts of epoxy resin, and 0.21 parts of dibenzoyl peroxide.
[0070] The preparation method is as follows:
[0071] 100 parts by weight of nano silicon nitride ceramic powder was mixed with 100 parts by weight of water, 1 part by weight of isopropoxy dioleyl (dioctyl phosphate) titanate was added, ball milled at 400 rpm for 2 hours, and dried to obtain coupled modified nano silicon nitride ceramic powder;
[0072] Dispersing the coupled modified nano silicon nitride ceramic powder in 100 parts by weight of anhydrous ethanol, adding 17 parts by weight of epoxy resin and 0.17 parts by weight of dibenzoyl peroxide, and mixing well to obtain slurry A;
[0073] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0074] Slurry A was dripped into slurry B, and the mixture was heated at 70°C until the anhydrous ethanol was completely evaporated to obtain slurry C;
[0075] The slurry C was heated at 85°C for 2 h to cure the epoxy resin, thereby obtaining slurry D.
[0076] Add 5 parts by weight of anhydrous ethanol, 4 parts by weight of epoxy resin and 0.04 parts by weight of dibenzoyl peroxide to slurry D, heat at 70° C. until the second anhydrous ethanol is completely evaporated, and then continue to heat at 85° C. for 3 h to cure the epoxy resin to obtain slurry E;
[0077] The slurry E was heated to 80° C. and then filtered. After filtering, the filter residue was washed five times with hot water at 60° C. and then dried to obtain a powdered thermosetting resin ceramic composite material.
[0078] Comparative Example 1
[0079] A nano ceramic material, the raw materials of which include, by weight, 100 parts of nano zirconium oxide ceramic powder, 23 parts of tripropylene glycol diacrylate, and 0.23 parts of dibenzoyl peroxide.
[0080] The preparation method is as follows:
[0081] Dispersing nano zirconium oxide ceramic powder in 100 parts by weight of anhydrous ethanol, adding 20 parts by weight of tripropylene glycol diacrylate and 0.2 parts by weight of dibenzoyl peroxide, and mixing well to obtain slurry A;
[0082] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0083] Slurry A was dripped into slurry B, and heated at 65°C until anhydrous ethanol was completely evaporated to obtain slurry C;
[0084] The slurry C was heated at 90° C. for 3 h to solidify the tripropylene glycol diacrylate to obtain slurry D.
[0085] 5 parts by weight of anhydrous ethanol, 3 parts by weight of tripropylene glycol diacrylate and 0.03 parts by weight of dibenzoyl peroxide were added to slurry D, and the mixture was heated at 65° C. until the second anhydrous ethanol was completely evaporated, and then heated at 90° C. for 2 h to cure the tripropylene glycol diacrylate, thereby obtaining slurry E;
[0086] The slurry E was heated to 60° C. and then filtered. After filtering, the filter residue was washed 5 times with hot water at 80° C., and then dried to obtain a nano-ceramic material.
[0087] Comparative Example 2
[0088] A nano ceramic material, the raw materials of which include, by weight: 100 parts of nano zirconium oxide ceramic powder, 1 part of gamma-glycidyloxypropyltrimethoxysilane, 23 parts of tripropylene glycol diacrylate, and 0.23 parts of dibenzoyl peroxide.
[0089] The preparation method is as follows:
[0090] 100 parts by weight of nano-zirconia ceramic powder was mixed with 100 parts by weight of water, 1 part by weight of γ-glycidyloxypropyltrimethoxysilane was added, ball-milled at 400 rpm for 2 hours, and dried to obtain coupled modified nano-zirconia ceramic powder;
[0091] Dispersing the coupled modified nano-zirconia ceramic powder in 100 parts by weight of water, adding 20 parts by weight of tripropylene glycol diacrylate and 0.2 parts by weight of dibenzoyl peroxide, and mixing well to obtain slurry A;
[0092] Dissolve 1 part by weight of polyvinyl pyrrolidone in 700 parts by weight of water to obtain slurry B;
[0093] Add slurry A dropwise into slurry B and mix well to obtain slurry C;
[0094] The slurry C was heated at 90° C. for 3 h to solidify the tripropylene glycol diacrylate to obtain slurry D;
[0095] 3 parts by weight of tripropylene glycol diacrylate and 0.03 parts by weight of dibenzoyl peroxide were added to slurry D, mixed, and heated at 90° C. for 2 h to cure the tripropylene glycol diacrylate to obtain slurry E;
[0096] The slurry E was heated to 60° C. and then filtered. After filtering, the filter residue was washed 5 times with hot water at 80° C., and then dried to obtain a nano-ceramic material.
[0097] Comparative Example 3
[0098] A nano ceramic material, the raw materials of which include, by weight: 100 parts of nano zirconium oxide ceramic powder, 1 part of gamma-glycidyloxypropyltrimethoxysilane, 20 parts of tripropylene glycol diacrylate, and 0.2 parts of dibenzoyl peroxide.
[0099] The preparation method is as follows:
[0100] 100 parts by weight of nano-zirconia ceramic powder was mixed with 100 parts by weight of water, 1 part by weight of γ-glycidyloxypropyltrimethoxysilane was added, ball-milled at 400 rpm for 2 hours, and dried to obtain coupled modified nano-zirconia ceramic powder;
[0101] Dispersing the coupled modified nano-zirconia ceramic powder in 100 parts by weight of anhydrous ethanol, adding 20 parts by weight of tripropylene glycol diacrylate and 0.2 parts by weight of dibenzoyl peroxide, and mixing well to obtain slurry A;
[0102] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0103] Slurry A was dripped into slurry B, and heated at 65°C until anhydrous ethanol was completely evaporated to obtain slurry C;
[0104] The slurry C was further heated at 90° C. for 3 h to solidify the tripropylene glycol diacrylate to obtain slurry D;
[0105] The slurry D was heated to 60° C. and then filtered. After filtering, the filter residue was washed 5 times with 80° C. hot water, and then dried to obtain a nano-ceramic material.
[0106] Comparative Example 4
[0107] Nano-zirconia ceramic powder without any treatment is used as the nano-ceramic material.
[0108] The testing methods and steps for the relevant performance of the products in the examples and comparative examples of the present application are as follows:
[0109] 1. Preparation of light-cured ceramic slurry
[0110] 100 parts by weight of the product, 20 parts by weight of trimethylolpropane trimethacrylate (photosensitive resin), 8 parts by weight of sodium ethylenediaminetetraacetate (dispersant) and 2 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (photoinitiator) were ball-milled and mixed for 5 hours to obtain a photocurable ceramic slurry. In order to facilitate the control of variables for comparison, the solid content of the photocurable ceramic slurry should be kept as close as possible during the evaluation.
[0111] 2. Calculation of solid content of light-cured ceramic slurry
[0112] The solid content of the photocurable ceramic slurry is calculated by the following formula:
[0113]
[0114] Where m f is the product mass, m1 is the photosensitive resin mass, m2 is the dispersant mass, and m3 is the photoinitiator mass.
[0115] 3. Evaluation of light-cured ceramic slurry
[0116] The slurry flow state is visually evaluated and divided into five levels: poor, poor, fair, good, and good.
[0117] 4. Viscosity test of light-cured ceramic slurry
[0118] The viscosity of the photocurable ceramic slurry was measured using a Fungilab Viscolead Adv R rotational viscometer.
[0119] 5. Evaluation of curing effect of light-cured ceramic slurry
[0120] Use a light-curing ceramic slurry to cure a single layer for 5 seconds on a light-curing machine, perform single-layer curing characterization, measure the curing depth, and evaluate the curing effect.
[0121] The relevant test results are shown in Table 1.
[0122] Table 1 Test results of Example 1 and Comparative Examples 1-5
[0123]
[0124] Compared with Example 1, the nano-zirconia ceramic powder in Comparative Example 1 has not undergone coupling modification. The composite rate of the nano-zirconia ceramic powder that has not been coupled modified and the thermosetting resin is not good, and there may be local incompatibility between the powder and the resin, that is, the specific core-shell structure of the present invention cannot be formed, the optical properties of the surface of the nano-zirconia ceramic powder are not well improved, and the curing effect is not ideal.
[0125] Compared with Example 1, Comparative Example 2 does not use the organic phase evaporation emulsification technology during the preparation process, and the slurry state of Comparative Example 2 is poor. Because the organic phase evaporation emulsification technology is not used, the nano-zirconia ceramic powder and the thermosetting resin are difficult to freely form balls in the water phase and cannot be tightly combined, resulting in the final material being not dense and difficult to prepare a high-solid content, low-viscosity photocurable ceramic slurry.
[0126] Compared with Example 1, Comparative Example 3 does not undergo secondary emulsification and curing during the preparation process. However, after organic phase evaporation, emulsification and curing in the preparation process, the material of Comparative Example 3 has a certain density and can be used to prepare a high-solid content, low-viscosity photocurable ceramic slurry. By comparing the curing depth, it can be seen that Example 1 has a better printing effect, indicating that the optical properties of the surface of the nano-zirconia ceramic powder are better improved after secondary emulsification and curing.
[0127] Compared with Example 1, Comparative Example 4 is a nano-zirconia ceramic powder that has not undergone any modification. It can be seen that the nano-zirconia ceramic powder that has not undergone any modification is difficult to prepare a high-solid content photocurable ceramic slurry and cannot be directly used in ceramic photocuring printing.
[0128] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A thermosetting resin ceramic composite material, characterized in that: The thermosetting resin ceramic composite material comprises a core and a shell, wherein the core comprises a composite microsphere formed of a first material, wherein the raw materials of the first material comprise: a coupling-modified nano-ceramic powder, a first thermosetting resin monomer and a first curing agent; the coupling-modified nano-ceramic powder is obtained by coupling-modifying nano-ceramic powder, wherein the coupling modification comprises the following steps: mixing the nano-ceramic powder with water, adding a coupling agent, ball milling, and drying to obtain the coupling-modified nano-ceramic powder; The shell layer includes a second thermosetting resin, the second thermosetting resin is formed by a second material, and the raw materials of the second material include: a second thermosetting resin monomer and a second curing agent; The preparation method of the thermosetting resin ceramic composite material comprises the following steps: Dispersing the coupled modified nano-ceramic powder in the first anhydrous ethanol, adding the first thermosetting resin monomer and the first curing agent, and mixing well to obtain slurry A; Dissolving the stabilizer in water to obtain slurry B; The slurry A is dripped into the slurry B, and heated until the first anhydrous ethanol is completely evaporated to obtain slurry C; Continue heating the slurry C to solidify the first thermosetting resin monomer to obtain slurry D; Adding a second anhydrous ethanol, the second thermosetting resin monomer and the second curing agent to the slurry D, heating until the second anhydrous ethanol is completely evaporated, and then continuing to heat to cure the second thermosetting resin monomer to obtain slurry E; The slurry E is sequentially subjected to hot filtration and hot water washing, wherein the temperature of the hot filtration is 60° C.-80° C., the temperature of the hot water is 60° C.-80° C., and then dried to obtain the thermosetting resin ceramic composite material.
2. The thermosetting resin ceramic composite material according to claim 1, characterized in that: In parts by weight, the nano-ceramic powder is 100 parts, the coupling agent is 0.5-2 parts, the first thermosetting resin monomer is 5-30 parts, the first curing agent is 0.05-0.3 parts, the second thermosetting resin monomer is 2-5 parts, and the second curing agent is 0.02-0.05 parts.
3. The thermosetting resin ceramic composite material according to claim 1, characterized in that: The nano-ceramic powder is at least one of nano-alumina ceramic powder, nano-zirconium oxide ceramic powder, nano-nickel oxide ceramic powder, nano-silicon carbide ceramic powder, nano-aluminum nitride ceramic powder and nano-silicon nitride ceramic powder; and / or, the coupling agent is at least one of methyl silane, epoxy silane, γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane and isopropoxy dioleyloxy (dioctylphosphoacyloxy) titanate; and / or, the first thermosetting resin monomer and the second thermosetting resin monomer are independently selected from at least one of tripropylene glycol diacrylate and epoxy resin; and / or, the first curing agent and the second curing agent are both dibenzoyl peroxide.
4. The thermosetting resin ceramic composite material according to claim 1, characterized in that: The diameter of the composite microspheres is 1-10 microns.
5. A method for preparing a thermosetting resin ceramic composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Performing the coupling modification on the nano-ceramic powder to obtain the coupling modified nano-ceramic powder; Dispersing the coupled modified nano-ceramic powder in the first anhydrous ethanol, adding the first thermosetting resin monomer and the first curing agent, and mixing well to obtain slurry A; Dissolving the stabilizer in water to obtain slurry B; The slurry A is dripped into the slurry B, and heated until the first anhydrous ethanol is completely evaporated to obtain slurry C; Continue heating the slurry C to solidify the first thermosetting resin monomer to obtain slurry D; Adding a second anhydrous ethanol, the second thermosetting resin monomer and the second curing agent to the slurry D, heating until the second anhydrous ethanol is completely evaporated, and then continuing to heat to cure the second thermosetting resin monomer to obtain slurry E; The slurry E is sequentially subjected to hot filtration and hot water washing, wherein the temperature of the hot filtration is 60° C.-80° C., the temperature of the hot water is 60° C.-80° C., and then dried to obtain the thermosetting resin ceramic composite material.
6. The method for preparing a thermosetting resin ceramic composite material according to claim 5, characterized in that: In parts by weight, the nano-ceramic powder is 100 parts, the coupling agent is 0.5-2 parts, the first anhydrous ethanol is 80-120 parts, the first thermosetting resin monomer is 5-30 parts, the first curing agent is 0.05-0.3 parts, the second anhydrous ethanol is 5-10 parts, the second thermosetting resin monomer is 2-5 parts, and the second curing agent is 0.02-0.05 parts.
7. The method for preparing a thermosetting resin ceramic composite material according to claim 5, characterized in that: In the slurry B, the mass ratio of the stabilizer to water is (1-3): (500-1000); and / or, the stabilizer is polyvinyl pyrrolidone or polyvinyl alcohol.
8. The method for preparing a thermosetting resin ceramic composite material according to claim 5, characterized in that: The curing time of the first thermosetting resin monomer is 2 hours to 4 hours, and the curing time of the second thermosetting resin monomer is 1 hour to 3 hours.
9. Use of the thermosetting resin ceramic composite material according to any one of claims 1 to 4 in ceramic photocuring printing.
Citation Information
Patent Citations
Purple sand ceramic slurry suitable for photocuring additive manufacturing and preparation method of purple sand ceramic slurry
CN118184302A
Ceramic slurry for photocuring forming of artificial bone scaffold and preparation method of ceramic slurry
CN118359428A
Titanium dioxide / polymer hollow microspheres and heat-insulating coating prepared from titanium dioxide / polymer hollow microspheres
CN118702880A